Seychelles : Second Review Under the policy coordination Instrument and Request for Modification of Targets-Press Release; and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
Economic developments since the completion of the first review under the Policy Coordination Instrument (PCI) in June 2018 have been broadly in line with expectations. The program is largely on track. Staff received renewed assurance from President Faure that the large infrastructure projects announced in his State of the Nation Address (SONA) in March 2018 would be implemented within the fiscal targets under the PCI.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet